Vapor-Phase Deoxygenation of Lactic Acid to Biopropionic Acid over Dispersant-Enhanced Molybdenum Oxide Catalyst - Li, Xinli; Pang, Jun; Zhang, Ju; Yin, Chunyu; Zou, Weixin; Tang, Congming; Dong, Lin (Industrial & engineering chemistry research, 2019)
Propionic acid obtained from fermentation-derived lactic acid has been appreciated since propionic acid is mainly used as a food preservative, satisfying a natural food idea. Vapor-phase deoxygenation of lactic acid to biopropionic acid over dispersant-dispersed molybdenum oxides was investigated in this work. It was found that different dispersants displayed different performances, and the N element in dispersants had a positive effect. MoO3 was soon reduced to MoO2 under the in situ hydrogen atmosphere, and the latter played an important role in catalytic conversion of lactic acid to propionic acid. The discriminating experiments revealed that propionic acid was formed mainly through direct deoxygenation of lactic acid (main path) and not hydrogenation of acrylic acid as an intermediate (minor path). Furthermore, only in situ hydrogen was efficient, and external hydrogen was hardly efficient during catalytic reaction. Under the base-free conditions, catalyst offered excellent activity and durability and efficiently reduced the acid-treatment section in product separation.